Effects of personal and professional factors on teachers' attitudes towards inclusion in preschool - Dias, Paulo C. (2016)
Attitudes towards inclusive education have a crucial place in the effective implementation of inclusion practices. The aim of this study was to explore teachers' attitudes towards inclusive education in preschool education in Portugal and to identify teachers' personal and professional variables that influence these attitudes. The data were collected from a sample composed of 68 preschool teachers working in mainstream schools located in urban and rural areas. The results indicated overall positive attitudes towards inclusion. Having previous personal contact with a person with special educational needs predicted more positive affective attitudes, whereas having previous experience teaching classes that included students with and without special educational needs predicted less positive behavioural intentions. From these results, we infer an emergent need for continuous training and for the promotion of positive attitudes among preschool teachers to achieve the successful implementation of inclusion at this educational level.